Legal dilemmas of maternal brain death during pregnancy - The Case of Marlise Munjoz - Drljača, Jagoda V (Glasnik Advokatske komore Vojvodine, 2020)
The subject of this article is a case that occurred in Texas in 2013 which has caused great debate between medical and legal profession and has stirred public concern. Marlisa Munoz, 14 weeks pregnant, suffered a massive pulmonary embolism resulted in a brain death. Marlisa’s will had been that in the case of irreversible brain damage, doctors didn’t somatically support her. Despite Marlisa’s will, announced by her husband Eric, and confirmed by her parents, doctors decided to keep her artificially maintained until delivery, or while the fetus is vital. The reason for this decision has been found in the Texas Advance Directives Act (TADA). The main problem with this regulation and interpretation thus set is collision between the rights of the individual who has made decision about their physical integrity and the right of the fetus to continue to develop. In this case, no account was taken of the brain anomalies and damages that fetus would have develop growing from week 14 inside brain death mother artificially maintained. The aim of this research is to analyze advance directives, whether the regulations derogate living will when the patient is pregnant woman, (un) justification for derogation, with special reference to the controversial TADA. In concluding considerations, I will analyze which legal and ethical dilemmas arise in these cases